PEMBENTUKAN DERIVATIF KATA BAHASA ARAB DALAM PERSPEKTIF MAZHAB KUFFAH - Arifuddin Arifuddin (Arabic Literature Department, 2016)
The construction of word in Arabic language had been done by the process of derivation, by looking into this process, the lexicon of Arabic language can be reached and also it can be developed by the period. This research will investigate the construction of Arabic derivative word in the perspective of Kufah Scholar. The data in this research was divided into certain theories and facts of language collected from the primary and secondary references. The primary reference included the main opus work from the Kufah scholars, such as: Al-Farra‟, and also some works from Al-Anbari who had been collected and noted many opinions belong to Kufah scholar during the confrontation with the Basrah scholar. An amount of the research results and some works of contemporary Arabic Grammarians had been become the secondary reference of this research. This research had been concluded that the process of derivation in Arabic word in the Kufah Scholar had many variants of patterns and the high forms. This condition was caused by the data of language which had been recognized wider range of Basrah scholar. The opinion of Kufah Scholar about the root or radical had the strong basis in the development of contemporary of linguistics, especially in the Semitic Language.